Plan de negocio para la creación de un centro estético especializado en niños y niñas de la ciudad de Quito - Peñafiel Gómez, Carolina Alexandra (2014)
Nowadays, in our country there is a trend by the consumers both men and women of any age to take care of their personal appearance. In this trend have been included boys and girls whose parents also seek to take care of their personal appearance. Regarding to this trends and needs, born the idea to offer the consumer a different and specialize service of esthetic center for children between 0 to 14 years old. It was determined through market research, that there is a demand that needs to be satisfy, as well as we obtain important data that supports that the market segment have great acceptance for this business plan. The strategy to enter to the market is established by the strategy of segmentation and positioning mainly based on differentiation in order to build competitive advantage. We are also going to handle a general marketing strategy based on the chain service-profit; this strategy is because our employees are the executors of the service and therefore must be satisfied and committed to their work For the service, the physical space, professionalism as well as the good treatment we offer, seeks to provide the quality, care and aseptic required by the consumer that needs a different treat according to their age. In the financial analysis we determine that the initial investment is USD 31.097,04 for the project implementation. Considering a normal scenario, with a leverage of 56,51%, is obtained an Internal Rate of Return-IRR of 48,65% and a Net Present Value-NPV of USD 63.685,20, this data demonstrates the financial viability of this project.